Catch rates of marine fish species from Shatt Al- Basrah Canal, Southern Iraq - Taher, Majid Makky; Resen, Amjed Kadhum; Mohamed, Sadiq Jawad (Iraqi Journal of Aquaculture, 2022)
Monthly fish samples were collected from one location at Shatt Al- Basrah Canal from July 2008 to June 2009, using coastal seine net of dimensions 80 m length and 8 m height with a mesh size 10×10 mm. Water temperature, salinity and water transparency were measured. Fishes were identified in the laboratory and total lengths and weights were measured. Catch per unit of effort was estimated for 22 species collected during the sampling period. The a biotic factors exhibited monthly fluctuations, especially in salinity and water temperature. The water temperatures were varied between 12 and 31.5 ºC, and the range of salinity gradient was 5.5-47.5 ppt., however the water transparency showed less variation (37.1-61 cm). Catch per unit of effort found to be zero in December, while the highest catch rate was 39.9 kg / h for Liza subviridis during July and the lowest was 0.02 kg / h for many species during several months. Basing on average as total, the highest average of catch rate was 5.89 kg / h for Liza subviridis, followed by 2.96 kg / h for Liza klunzingeri, while the lowest was 0.14 kg / h for Brachirus orientalis. The two mugilid species Liza subviridis and Liza klunzingeri) consisted 69 % of the overall catch rate and 75 % of the commercial catch rate. The catch rate of Johnius belangerii showed the highest significant positive correlation coefficient (0.72) with temperature, however highest non significant negative correlation was -0.37 for Sillago arabica. For salinity, the results revealed that the highest significant positive correlation was 0.74 with the catch rate of Johnius belangerii and thehighest significant negative correlation (-0.54) with Sillago sihama. The correlations with water transparency showed that the highest significant positive correlation was 0.66 with Acanthopagrus latus and highest non significant negative correlation (-0.39) with Sillago arabica.